2017
DOI: 10.3390/cryst7080233
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive In Situ Study of Plastic Deformations in Diamonds: X-ray Diffraction Topography and µFTIR Mapping of Two Super Deep Diamond Crystals from São Luiz (Juina, Brazil)

Abstract: Diamonds from Juina, Brazil, are well-known examples of superdeep diamond crystals formed under sublithospheric conditions and evidence would indicate their origins lie as deep as the Earth's mantle transition zone and the Lower Mantle. Detailed characterization of these minerals and of inclusions trapped within them may thus provide precious minero-petrogenetic information on their growth history in these inaccessible environments. With the aim of studying non-destructively the structural defects in the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Various zones of the crystals have traces of plastic deformations as a series of thin lines (deformation lamellae) intersecting different growth zones of the crystals. These features of the internal structure have also been detected in many previously described super-deep diamonds derived from different depth regimes [10,12,15,20,56,[64][65][66].…”
Section: Cathodoluminescencesupporting
confidence: 69%
See 2 more Smart Citations
“…Various zones of the crystals have traces of plastic deformations as a series of thin lines (deformation lamellae) intersecting different growth zones of the crystals. These features of the internal structure have also been detected in many previously described super-deep diamonds derived from different depth regimes [10,12,15,20,56,[64][65][66].…”
Section: Cathodoluminescencesupporting
confidence: 69%
“…There is little data regarding the internal structure of super-deep diamonds. Agrosi et al [20] studied the internal structures of two super-deep diamond samples non-destructively by X-ray diffraction topography (XRDT) and micro Fourier transform infra-red spectroscopy (µFTIR). Results showed that both samples are affected by complex plastic deformation.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, numerous investigations have been undertaken to extract and decipher this diamond message. In their contribution, Giovanna Agrosi, Gioacchino Tempesta, Giancarlo Della Ventura, Mariangella Cestelli Guidi, Mark Hutchison, Paolo Nimis, and Fabrizio Nestola studied diamond crystals from Sao Luiz (Juina, Brazil) [6]. Diamonds from Juina, Brazil, are well-known examples of superdeep diamond crystals formed under sublithospheric conditions at depths greater than 400 km [7].…”
Section: Some Facets Of Natural Diamond Crystalsmentioning
confidence: 99%
“…Spectroscopic techniques and especially Synchrotron-based Fourier-Transform Infrared microspectroscopy (S-FTIR) have been used in geosciences for decades 1 – 3 . S-FTIR has notably been proven efficient for determining at the micrometer scale the mineral, fluid and organic phases contained in interplanetary dust particles, meteorites and terrestrial material 4 10 . When characterizing samples at micrometer scale, user is tracking phases with a very limited spatial distribution and more or less low concentrations.…”
Section: Introductionmentioning
confidence: 99%